THE SACRED HERITAGE OF THE GALITIC METROPOLITAN: HISTORICAL-CULTURAL AND RELIGIOUS AND PHILOSOPHICAL ASPECTS - Nadia Rusko; Natalia Kontsur-Karabinovych (Scientific Journal of Polonia University, 2023)
Formulation of the problem. The relevance of the article is determined by the specificity of the study of the sacred heritage of the Galician metropolis, because it was thanks to the center of the metropolis that it was possible to preserve the national and religious identity. The purpose of the article is to determine the role of the Galician Metropolis in preserving the historical memory, cultural and religious identity of Ukrainians. The novelty of the article is determined by the fact that, for the first time, the national peculiarities of the sacred heritage of Galicia, their influence on the value-moral potential and anthropological peculiarities of the formation of religious objectification of the Western region of Ukraine were deeply investigated. Today, when Ukraine is facing new challenges of the cultural, historical, religious, philosophical, political, and economic dimensions, it is very important to show the role of valuable, sacralized, transcendent factors in the formation of national sakrumy through the study of the problems of spiritual heritage. This article asserts that the worldview and mental core of Ukrainian national culture is visualized in sacred places, which are the basis of spirituality and value identity of the region. It was found that they have not only an original, unique cultural content and form, but also their own spiritual territory, where they affirm and reveal the traditional values of the metaphysics of culture, where a person correlates himself with fundamental spiritual values, the Absolute, with higher meanings, national shrines.